2020
DOI: 10.18821/0869-2084-2020-65-6-347-352
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Forms of Pd-1 and Pd-L1 in Blood Plasma of Gastric Cancer Patients and Their Associations With Clinical and Morphological Characteristics of the Disease

Abstract: Results of comparative ELISA investigation of pretreatment sPD-1 and sPD-L1 content in blood plasma of 100 gastric cancer patients at various disease stages aged 25 to 81 years are presented. Control group included 60 practically healthy donors aged 18 - 68 years. Plasma sPD-L1 concentrations did not differ between gastric cancer patients and control group, and sPD-1 levels were statistically significantly lower in patients than in healthy donors (p<0.0001). Positive correlation (R=0.38; p=0.003) was reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Gershtein et al reported similar results regarding sPD-1 lower levels in GC, 27 while sICOS previous studies in GC are sparse. We did not find a significant association between sICOS and sPD-1 expression and Lauren histologic type or the WHO grade of differentiation.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Gershtein et al reported similar results regarding sPD-1 lower levels in GC, 27 while sICOS previous studies in GC are sparse. We did not find a significant association between sICOS and sPD-1 expression and Lauren histologic type or the WHO grade of differentiation.…”
Section: Discussionmentioning
confidence: 67%
“…These findings suggest that there is a lower production of sICOS and sPD‐1 by activated lymphocytes in GC, reflecting a T cell activation dysregulated environment as a response to gastric tumor cells. Gershtein et al reported similar results regarding sPD‐1 lower levels in GC, 27 while sICOS previous studies in GC are sparse. We did not find a significant association between sICOS and sPD‐1 expression and Lauren histologic type or the WHO grade of differentiation.…”
Section: Discussionmentioning
confidence: 68%
“…Recent evidence has shown that patients with GC have higher serum soluble PD-L1 (sPD-L1) concentrations than healthy controls. Moreover, both elevated tissue PD-L1 and serum sPD-L1 were independent prognostic factors for poor OS and poor DFS in GC patients who underwent surgery [70][71][72]. Lymphocyte activation gene 3 (LAG3) is a checkpoint receptor localized on activated T cell surfaces and NK cells.…”
Section: Circulating Biomarkersmentioning
confidence: 99%